Regional developments: East and Southeast Asia [in 2025 GFPR] - Chen, Kevin Z.; Zhou, Yunyi; Kou, Ke; Fan, Shenggen (International Food Policy Research Institute, 2025)
Over the past half-century, the food systems of East and Southeast Asia have been shaped by economic growth and structural transformation, extreme weather events, and unique agricultural landscape and value chain dynamics. This chapter examines how aligning research outputs, financial programs, and regional cooperation initiatives with national policy frameworks in the region has led to improvements in food security, nutrition, and livelihoods in the region’s countries, though important challenges remain. Looking ahead, food systems transformation in the region will require a multisectoral approach that includes cross-cutting foresight and integrated approaches that combine disruptive technologies, participatory governance, and scalable solutions supported by sustainable financing mechanisms.